Evolution of Minimally Invasive Surgical Aortic Valve Replacement at a Veterans Affairs Medical Center. Issue 3 (May 2019) - Liang, Norah E.; Wisneski, Andrew D.; Wozniak, Curtis J.; Ge, Liang; Tseng, Elaine E.
Abstract : Objective: The majority of minimally invasive surgical aortic valve replacements (MIAVRs) are performed at high-volume cardiac surgery centers. However, outcomes at lower volume federal facilities are not yet reported in the literature and not captured in the national Society of Thoracic Surgeons (STS) database. Our study objective was to describe the evolution of MIAVR at a Veterans Affairs Medical Center (VAMC). Methods: A single-center retrospective cohort study was performed of 114 patients who underwent MIAVR for isolated aortic valvular disease between January 2011 and August 2018. Preoperative STS risk factors were determined and perioperative outcomes were analyzed. Results: By 2016, 100% of isolated surgical aortic valve replacements were performed as MIAVRs at our VAMC. Introduction of automatic knot-fastening devices, single-shot del Nido cardioplegia, and rapid deployment valves decreased aortic cross-clamp (AXC) times from a median of 96 (interquartile range [IQR]: 84 to 103) to 53 minutes (38 to 61, P < 0.001, Kruskal–Wallis). Thirty-day mortality was 0.9%. Median length of hospital stay was 9 days (7 to 13). Postoperative atrial fibrillation occurred in 54% of patients, stroke occurred in 1.8% of patients, and 7.1% of patients required permanent pacemakers. Transition to rapid deployment valves decreased postoperative mean pressure gradient from median 14 mmHg (10 to 17) to 7 mmHg (4.7 to 10, P < 0.001, Mann–Whitney). At median 1.5-year follow-up echocardiogram, mean gradient was 10.8 mmHg with mild paravalvular leak rate of 1.8%. Conclusions: Facilitating technologies decreased operative times during MIAVR adoption at our VAMC. For patients with isolated aortic valve pathology, MIAVR can be performed with low morbidity and mortality at lower volume federal institutions, with outcomes comparable to those reported from higher volume centers.